2021
DOI: 10.2147/ijgm.s304837
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA UCA1 Accelerates the Progression of Ulcerative Colitis via Mediating the miR-331-3p/BRD4 Axis

Abstract: Background Ulcerative colitis (UC) has become one of the fastest-growing severe diseases worldwide with high morbidity. This research aimed to explore the function of lncRNA UCA1 in UC progression. Methods RT-qPCR analysis was used to examine the expression of UCA1 level in colonic mucosa tissues of UC patients. Then, fetal human cells (FHCs) were stimulated by LPS to induce inflammatory injury. CCK-8, flow cytometry and ELISA were adopted to determine the influence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Enduring inflammation of the colon epithelia has been linked to the initiation of colorectal cancer [ 21 ]. Recent studies revealed a different expression pattern of ncRNAs between healthy, inflamed, adenocarcinoma and cancerous tissue of colonic tissues suggesting that ncRNAs may be promising prognostic and diagnostic markers and therapeutic targets [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Enduring inflammation of the colon epithelia has been linked to the initiation of colorectal cancer [ 21 ]. Recent studies revealed a different expression pattern of ncRNAs between healthy, inflamed, adenocarcinoma and cancerous tissue of colonic tissues suggesting that ncRNAs may be promising prognostic and diagnostic markers and therapeutic targets [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, H19 was demonstrated to locate in the cytoplasm through the lncATLAS website prediction and nuclear/cytosol fractionation assay, suggesting that H19 could act as a ceRNA to play a role in UC. Prior research unveiled that miR-331-3p depletion aggravates inflammation and apoptosis in UC [17]. The binding relationship of H19 and miR-331-3p was testified via RNA pull-down and dual-luciferase assays.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, target miRNAs of H19 were predicted with the aid of the Starbase database. Prior studies have demonstrated that miR-331-3p is involved in inflammatory responses in multiple diseases and plays a crucial role in UC development [15,17]. Hence, we se-Fig.…”
Section: H19 Negatively Regulated Mir-331-3pmentioning
confidence: 97%
See 1 more Smart Citation